Workshop Dan Pendampingan Pembuatan Game Edukasi Berbasis Android Bagi Guru SDN 2 Cakranegara - Muhammad Makki; Dyah Indraswati; Muhammad Erfan; Aisa Nikmah Rahmatih; Vivi Rachmatul Hidayati (Jurusan Ilmu Pendidikan, FKIP, Universitas Mataram, 2021)
The Covid-19 pandemic has led to policies that make teachers and students have to adapt the face-to-face learning model to online learning. The teacher of SD N 2 Cakranegara admits that there are limitations to the variety of audio-visual learning media used. The teachers also don't know and have never tried to develop game games with learning content, even though Android-based games are very possible to be developed and accessed portable on smartphones, the majority of which are already owned by teachers and students. The provision of workshops and assistance in making Android-based educational games for SD N 2 Cakranegara teachers aims to improve skills in creating and developing learning media in the form of educational games and maximizing the use of smartphones. The targeted output in this service activity is the existence of educational games that are ready to be used for the online learning process through appsgeyser.com and quickappninja.com.